Regional Analysis of Stock Returns Effect of Earnings Management and Corporate Tax Avoidance - Kwakye, Teddy Ossei; Adu-Poku, Manfred; Cudjoe, Mawuena Akosua; Coffie, William; Amidu, Mohammed (Journal of Accounting and Finance, 2024)
This study aims to investigate the relationship between earnings management, tax avoidance, and stock returns across different economic regions in the world. We used firm-level secondary data of selected listed firms from regions namely Europe, North America, Afro-Asia, Australia and South America, consisting of 39,490 non-financial listed firms spanning across 45 countries from 1995 to 2013. We employ comprehensive analysis using a two-step system GMM regression, with Windmeijer-corrected standard errors, small sample adjustment, and orthogonal deviation. The study finds that accounting information quality and tax avoidance influences stock returns, but the relationship varies across regions. The study’s findings have practical implications for policymakers and market participants. The results highlight the importance of improving accounting standards and transparency to provide reliable financial information and support investor decision-making. Policymakers and market participants should consider regional variations in accounting practices and tax strategies when formulating policies and conducting investment analysis.